“WAITING LIST” PROBLEMS: REASONS FOR PATIENTS’ REFUSAL OF PLANNED CORONARY ARTERY BYPASS GRAFT SURGERY - A. N. Sumin; A. V. Osokina; A. M. Kochergina (Российский кардиологический журнал, 2012)
Aim. To identify the reasons for the patients’ refusal to undergo a planned coronary artery bypass graft (CABG) surgery, after being put on the “waiting list” for the intervention. Material and methods. From January 2010 to March 2011, 1,057 patients (100%) were put on the CABG “waiting list” of the Research Institute of Complex Cardiovascular Problems, Kemerovo. Due to various reasons, 74 individuals refused to undergo the surgery (7%). The reasons for refusal were identified during a telephone interview of 65 patients; for 51 (4,8%), the refusal was confirmed. The final analysis included 51 patients – the main group, who refused the intervention due to various reasons. Clinical and anamnestic parameters of these patients were compared to those of the control group (51 consecutive patients hospitalised for the planned CABG). For both groups, the primary medical documentation was used to determine the waiting period between establishing the need for CABG and the planned hospitalisation, as well as to record the results of coronary artery angiography (CAG). In addition, we analysed the results of echocardiography (EchoCG; left ventricular ejection fraction, LVEF) and the levels of creatinine, urea, potassium, sodium, glucose, haemoglobin, white and red blood cells, and erythrocyte sedimentation rate, measured before CAG. Results. The most prevalent refusal reasons were fear of the intervention (35,3%) and good self-perceived health (33,3%). The third most common reason was no explanation of the intervention importance to the patient by the doctor (9,8%). In the control group, the hospitalisation for planned CABG significantly more often took place within one month after CAG, compared to the main group (n=17 and 6, respectively; p<0,01). By contrast, in the main group, hospitalisation for CABG was significantly more often planned for the sixth month after CAG, compared to the control group (n=12 and 4, respectively; p=0,02). According to the multivariate analysis results, waiting for the intervention for longer than one month was associated with an increased likelihood of refusal. Conclusion. The prevalence of CABG refusal among “waiting list” patients was 4,8%. The main reasons for refusal included no symptoms of coronary heart disease progression, fear of intervention, and no explanation of the intervention necessity. The key additional factor associated with refusal was the waiting time over one month. Russ J Cardiol 2012, 5 (97): 63-69 Key words: coronary heart disease, coronary artery bypass graft surgery, waiting list order.><0,01). By contrast, in the main group, hospitalisation for CABG was significantly more often planned for the sixth month after CAG, compared to the control group (n=12 and 4, respectively; p=0,02). According to the multivariate analysis results, waiting for the intervention for longer than one month was associated with an increased likelihood of refusal. Conclusion. The prevalence of CABG refusal among “waiting list” patients was 4,8%. The main reasons for refusal included no symptoms of coronary heart disease progression, fear of intervention, and no explanation of the intervention necessity. The key additional factor associated with refusal was the waiting time over one month.